UF/IFAS Nutrient Management Series: Computational Tools for Field Implementation of the Florida Phosphorus Index - Okeechobee Watershed Area - G. Wade Hurt; Rao S. Mylavarapu; S. P. Boetger (EDIS)
Circular 1339, a 48-page document by G. W. Hurt, R. S. Mylavarapu, and S. P. Boetger, provides many tables with numerical values for each of the various factors listed in the Florida P Index to be used in computations to aid planners in designing conservation plans related to land application of animal wastes. Contents: Introduction -- Components of the P Index -- Field Evaluation and Implementation for Okeechobee County -- Resulting P Index -- References -- Appendix I: Runoff, Leaching Potentials, and K-Factors for County Soils. Published by the UF Department of Soil and Water Sciences, June 2006.